Tiempos d etemperaturas de torrefacción en almendras de tres variedades de cacao (Theobroma cacao L.) nacional, trinitario y forastero, para la obtención de NIBS en la finca experimental "La Represa" - Barzola Cárcamo, Jasson Abelardo (2019)
The present investigation was carried out in the Experimental Farm "La Represa", and in the Bromatological Laboratory, property of the Universidad Técnica Estatal de Quevedo, province of Los Ríos, as objective was determined times and temperatures of torrefaction in almonds of three varieties of cocoa (Theobroma cacao L.), National, Trinitario and Forastero, to obtain nibs in the “La Represa” experimental farm, through physical and sensory analysis. A completely randomized experimental design (DCA) was applied, within a 3x2 factorial arrangement, with four repetitions. To compare the means of the treatments, the Tukey test was used at 5% significance (p≤ 0.05). In the statistical analysis for the pH, humidity, organic matter and dry matter variables of the roasted cocoa nibs, there was no significant statistical difference for the factor of time and temperature and in the interactions between the different varieties of cocoa National, Trinitario and Forastero. Indeed, in the sensory properties (odor, taste, color and texture), it was determined that T1 obtained the highest preference index with 36%, followed by T2 with 22% and T5 registered the lowest preference value of 9 %. Key words: Cocoa, Nibs, time, temperature.